Implementation of the Natural Flow Paradigm to Protect Dwarf Wedgemussel (Alasmidonta heterodon) in the Upper Delaware River. (14th December 2016) - Parasiewicz, P.; Castelli, E.; Rogers, J. N.; Vezza, P.; Kaupsta, A.
Abstract: This paper demonstrates the use of a multiplex habitat model for flow management criteria development compliant with the natural flow paradigm using the Upper Delaware River (NY/PA—USA) as an example. The goal of this study was to identify strategies to protect and support the recovery of the dwarf wedgemussel populations in the mainstem Delaware River. We quantified potential habitat, developed instreamflow recovery scenarios and modelled the scenario outcomes. Mesohabitat simulation model and River2D have been used to allow the transfer of suitability criteria between scales. Habitat time series were investigated with the help of the uniform continuous under threshold technique to establish natural habitat stressor thresholds. Exceedance of persistent and catastrophic durations results in habitat stress days (HSD). HSD served as a metric for the comparison of four flow and two habitat management scenarios. The greatest habitat improvements were accomplished through increasing the boundary Reynolds number, hence increasing the river bed diversity. The introduction of naturalized flows into the model did not cause any significant reduction of HSD, demonstrating that optimizing suitable habitat for dwarf wedgemussel may not be achieved without including morphological improvements. Both minimum and pulsed flow augmentation strategies were found to nullify rare stress days in our models. Our study found that, at a minimum, a pulsed flow regime would need to be created to promote the development of populations beyond the current mussel beds. To accomplish protection and enhancement of habitat fully, channel improvements that reduce boundary Reynolds number appear necessary. These recommendations are intended to create a starting point in the adaptive flow management process for the Upper Delaware River. Copyright © 2016 John Wiley & Sons, Ltd.